Human Resource Management Practices impacting on Turnover Intention: Evidence from IT Employees in Bangladesh - Kamruzzaman, Md; Rauf, Md Abdur; Shamim, Dr Md Mahfuzul Islam (International Journal on Economics, Finance and Sustainable Development, 2022)
Organisations' most valuable resource is their human resources, and keeping excellent workers on board is essential for those looking to gain a competitive edge. Organisations use a variety of human resource management (HRM) strategies to control employee churn. The term "Generation Y" refers to the particular generation, often known as the "millennial" or "Internet generation," that was born between the 1980s and the early 1990s. This research investigates the connection between generation Y employee turnover intention and HRM practices. The HRM practices included in the study are perceived training, compensation, performance appraisal, and turnover intention since they are seen to be the key practices with the most effects on an organisation's success. In Bangladesh's private sector, Gen Y's inclination to leave the job is a serious issue.